Answer :

A =

A^{2} =

=

Now, A^{2} = λA – 2I

= λA = A^{2} + 2I

=

= λ

=

= = 3 or λ = 1

So, A^{2} = A – 2I

Multiply by A ^{– 1} both sides

= A.A. A ^{– 1} = A. A ^{– 1} – 2I. A ^{– 1} = 0

= 2A ^{– 1} =

Hence, A ^{– 1} =

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers